2012
DOI: 10.1100/2012/503945
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bone Resorption Markers after Parathyroidectomy for Renal Hyperparathyroidism: Correlation Analyses for the Cross-Linked N-telopeptide of Collagen I and Tartrate-Resistant Acid Phosphatase

Abstract: Patients on long-term dialysis may develop secondary hyperparathyroidism (SHPT) with increased serum concentrations of bone resorption markers such as the cross-linked N-telopeptide of type I collagen (NTX) and type-5b tartrate-resistant acid phosphatase (TRAP). When SHPT proves refractory to treatment, parathyroidectomy (PTX) may be needed. Renal patients on maintenance HD who received PTX for refractory SHPT (n = 23) or who did not develop refractory SHPT (control subjects; n = 25) were followed prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This result is in concordance with many other trials where a significant postoperative decrease in TRAP5b levels was reported [31, 32, 37-39]. As reported by Hung et al [39], the decrease continues for several weeks after surgery. Therefore, TRAP5b seems to be an important and reliable marker of bone metabolism in patients with sHPT.…”
Section: Discussionsupporting
confidence: 82%
“…This result is in concordance with many other trials where a significant postoperative decrease in TRAP5b levels was reported [31, 32, 37-39]. As reported by Hung et al [39], the decrease continues for several weeks after surgery. Therefore, TRAP5b seems to be an important and reliable marker of bone metabolism in patients with sHPT.…”
Section: Discussionsupporting
confidence: 82%
“…The percentage of urine NTX tested decreased from 29.7% to 12.2% for bone metabolic markers. Serum NTX has less diurnal variation than urine NTX but tends to be higher with decreased renal function [ 19 , 20 ]. Because urine NTX requires measurement of the second urine sample early in the morning, if the test is to be performed strictly, it is necessary to give the patient a urine test container in advance [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In postmenopausal women, effective bisphosphonate treatment results in a quantifiable reduction in urinary excretion of N-telopeptide of type I collagen and improvement in bone density [42]. The bone lining cells prevent pyrophosphate from entering the structure by cleaving it with alkaline phosphatase [43].…”
Section: Bisphosphonates In Advanced Ckdmentioning
confidence: 99%
“…Bisphosphonates are standard drugs for osteoporosis and are like pyrophosphate compounds ( Figure 1 ), which are crucial endogenous inhibitors of ectopic mineralization. In postmenopausal women, effective bisphosphonate treatment results in a quantifiable reduction in urinary excretion of N-telopeptide of type I collagen and improvement in bone density [ 42 ]. The bone lining cells prevent pyrophosphate from entering the structure by cleaving it with alkaline phosphatase [ 43 ].…”
Section: Bisphosphonates In Advanced Ckdmentioning
confidence: 99%